Taller de resiliencia para mejorar las capacidades socio afectivas en directivos y docentes de las instituciones educativas públicas de la red educativa rural las Amazonas Maynas 2023 - Pizango Pisco, Pamela (2025)
The research aims to assess the impact of the Resilience Workshop on improving the socio-emotional competencies of administrators and teachers in the Rural Educational Network Las Amazonas during 2023. An evaluative methodology was utilized, featuring a pre-experimental design with univariate, longitudinal, and field approaches, involving a single group with pretest and posttest assessments. The sample consisted of 48 teachers and administrators, and the data collection instrument was validated through expert judgment. Results reveal significant differences in the means and standard deviations of socio-emotional competencies and their components before and after the workshop. Means increased substantially, from 40.79 to 60.33 in the socio-emotional variable. Specific competencies also exhibited notable increases: emotion regulation from 8.75 to 15.08, personal motivation from 8.96 to 15.21, emotion recognition from 9.38 to 14.79, and emotional establishment from 8.75 to 15.25. Standard deviations remained consistent, indicating that the observed improvements are attributable to the Resilience Workshop intervention.